2020
DOI: 10.1093/ofid/ofaa439.738
|View full text |Cite
|
Sign up to set email alerts
|

544. Severe COVID-19 in Children and Young Adults in the Washington DC Metropolitan Region

Abstract: Background Children and young adults were initially reported as largely spared from severe complications of SARS-CoV-2 infection, but the impact to this population has been significant. Methods This observational retrospective cohort study includes 420 symptomatic children and young adults with lab confirmed SARS-CoV-2 infection treated between March 15 and June 16, 2020 at Children’s National Hospital in Washington DC. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
59
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 0 publications
9
59
0
2
Order By: Relevance
“…48 Several studies have observed no difference in obesity rates between children with mild vs. severe COVID-19 disease. [50][51][52] While obesity in paediatric patients hospitalized for COVID-19 is not more frequent than in the general paediatric population, COVID-19 disease severity may be associated with obesity, as in adults. One report of 50 paediatric patients hospitalized with COVID-19 identified obesity as a risk factor for mechanical ventilation.…”
Section: Current Evidence Does Not Suggest That Central Hormone Deficiencies Increase Risk Of Acquiring Sars-cov-2 Infectionmentioning
confidence: 99%
“…48 Several studies have observed no difference in obesity rates between children with mild vs. severe COVID-19 disease. [50][51][52] While obesity in paediatric patients hospitalized for COVID-19 is not more frequent than in the general paediatric population, COVID-19 disease severity may be associated with obesity, as in adults. One report of 50 paediatric patients hospitalized with COVID-19 identified obesity as a risk factor for mechanical ventilation.…”
Section: Current Evidence Does Not Suggest That Central Hormone Deficiencies Increase Risk Of Acquiring Sars-cov-2 Infectionmentioning
confidence: 99%
“…10 Also a multi-system inflammatory syndrome is reported among children by WHO. 12 The report describes that, clusters of children and adolescents requiring hospital admission with a multisystem inflammatory condition, and some features similar to Kawasaki disease and toxic shock syndrome, in continents like Europe and North America 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Despite being an unusual manifestation, the increase in the number of reported associations between Kawasaki Disease (KD) and COVID-19 in children raises new concerns about its consequences. 5,6 Search Methods: In order to develop a nonsystematic narrative review, we executed literature searches in multiple databases (Google Scholar, PubMed, SciELO, and Medscape) with no time restriction for articles published in English. Search terms included the keywords: "Sars-CoV-2", "COVID-19", "Kawasaki-like", "MIS-C", "PIMS-TS" and "Autoimmune disease".…”
mentioning
confidence: 99%